STRATEGI BISNIS PT PERTAMINA (PERSERO) DALAM MENGHADAPI FLUKTUASI HARGA MINYAK DUNIA AKIBAT GEJOLAK POLITIK TIMUR TENGAH TAHUN 2011-2015 - Wisnuwardhani, Nastiti (Global and Policy Journal of International Relations, 2017)
ABSTRACTThe research describes about Pertamina's business strategys are in the middle of world oil prices fluctuation due to Middle East political turmoil 2011-2015. The background of the problem is the Middle East political turmoil resulting fluctuation in world oil prices. These fluctuations cause the country that depend on the area affected by the fluctuation problem. In the face of such problems, Pertamina uses business strategy to deal with fluctuations in world oil prices. The question that arises in this research is how Pertamina’s business strategy in the face of in world oil prices fluctuation due to political turmoil the Middle East in 2011-2015 ?. The question was examined by the concept of a business strategy. Business strategy implemented by Pertamina through innovation and market development or expansion. Based on the final results of the research, we concluded that Pertamina's business strategys are in the middle of world oil prices fluctuation in 2011-2015 through product innovation and gas refinery and market development in the Middle East.Keywords : Fluctuation, Product Inovation, Expansion, Middle EastDOI: https://doi.org/10.33005/jgp.v5i01.1901